The Politics of (Not) Giving a Sh*t: Understanding the Invisibilization of Queer South Asian Women in Pride Toronto - Patel, Sonali (Université d'Ottawa / University of Ottawa, 2021)
This thesis builds on the findings of my previous study, which established that queer South Asian women (QSAW) feel invisibilized in Toronto’s LGBTQ+ community (see Patel, 2019). The present study critically investigates the operation and cultural reproduction of power in organizational practices that invisibilize QSAW within Pride Toronto™, as a means of diagnosing the problem in mainstream LGBTQ+ organizations more broadly. The following research question is explored: How do the cultural underpinnings of Pride Toronto™ contribute to the invisibilization of queer South Asian women in the broader LGBTQ+ community? This critical ethnography substantiates the invisibilization of QSAW in the LGBTQ+ community as an institutionalized form of identity-based violence. This study rejects the argument that invisibility is exclusively felt by QSAW. Instead, this thesis demonstrates that QSAW are invisibilized by the willful negligence of dominant actors in knowledge practices, as well as assimilationist politics that mandate outness, which invalidate and exclude QSAW. This study further finds that QSAW remain invisibilized in the broader LGBTQ+ community as a result of Pride organizations branding as diverse and inclusive, while simultaneously advancing colonial knowledge about queer identities and ideologies that re-write the narratives of QSAW in mainstream LGBTQ+ discourse.
Keywords: Invisibilization; Identity-Based Violence; Queer South Asian Women; LGBTQ; Critical Ethnography